2011
DOI: 10.1016/j.jnucmat.2010.12.156
|View full text |Cite
|
Sign up to set email alerts
|

In situ observation of damage structure in ODS austenitic steel during electron irradiation

Abstract: The oxide dispersion strengthening method was applied to an austenitic stainless steel based on SUS316 by mechanical alloying with additions of minor alloying elements. This ODS austenitic stainless steel was electron-irradiated to investigate the damage structure.Microstructural observation revealed that ODS austenitic stainless steel has a fine distribution of complex oxides. The in-situ observation during electron irradiation showed that both dislocation loops and small cavities nucleated at the interface b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 9 publications
2
27
0
Order By: Relevance
“…This explains why oversized defects lead to many small voids rather than few large ones. These observations also suggest that if any oversized solutes used in the production of ODS steels, such as Y, Hf, and Ti, remain dissolved in the Fe matrix they would contribute to the observed radiation-damage resistance by providing recombination sites in addition to those at the oxide nanoparticle surfaces [7,8].…”
Section: Vacancy Clustering and Void Nucleationmentioning
confidence: 87%
See 2 more Smart Citations
“…This explains why oversized defects lead to many small voids rather than few large ones. These observations also suggest that if any oversized solutes used in the production of ODS steels, such as Y, Hf, and Ti, remain dissolved in the Fe matrix they would contribute to the observed radiation-damage resistance by providing recombination sites in addition to those at the oxide nanoparticle surfaces [7,8].…”
Section: Vacancy Clustering and Void Nucleationmentioning
confidence: 87%
“…Such a low value means that a newly dissociated vacancy is much more likely to return to the solute than be lost to the general matrix (making an ω 0 jump) and it is reasonable to ask why this does not significantly suppress diffusion through the factor F (ω 4 /ω 0 ) in Eq. (8). However, even in the limit where the vacancy always returns, that is, ω 4 /ω 0 → +∞, F remains above zero at 2/7.…”
Section: Vacancy-mediated Solute Diffusionmentioning
confidence: 95%
See 1 more Smart Citation
“…The helium implantation increases the rate of void swelling and it tends to form coarse precipitates. Helium atoms act as nucleation sites of cavities 18 . Zhang 12 , et al have also reported the instability of phases due to irradiation.…”
Section: Void Swellingmentioning
confidence: 99%
“…In ODS316, the cavities evolve at matrix and cluster interface. The interface between oxide and matrix act as sink for cavities in ODS316 alloy 18 .…”
Section: Void Swellingmentioning
confidence: 99%